(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Mercury UV-C light sources are long known to be efficient for microbial inactivation and have been widely used. At the same time, the radiation, if used in inappropriate doses and spectral regimes, can also cause harmful effects to human tissue. The aim of the study was to evaluate the applicability of the novel UV light sources from thallium – antimony at different UV-C. For the research specially made light sources were produced. The influence of UV-C radiation in the range of 200 - 280 nm was tested on Gramnegative bacterium Escherichia coli, both with mercury and thallium. More than 99.99 % inactivation of E. coli cells was obtained after 10 min contact time for thallium – antimony UV-C light source, demonstrating the potential of the produced lamps.